2009
DOI: 10.1063/1.3103289
|View full text |Cite
|
Sign up to set email alerts
|

An acoustic emission study of the effect of a magnetic field on the martensitic transition in Ni2MnGa

Abstract: Acoustic emission measurements during the martensitic transition of a Ni–Mn–Ga magnetic shape-memory alloy reveal the intermittent and jerky character of the transition. The distribution of the amplitude of the acoustic emission events shows power law behavior, which reflects the absence of characteristic scales in the process. In this paper we show that the distribution is affected by an applied magnetic field, which proves that the transition dynamics is strongly influenced by magnetostructural coupling taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Our results can also be compared with acoustic emission measurements of Ludwig et al [2], as well as Niemann et al [3] where α = 2.6 and ε = 1.75 [2] as well as ε = 1.9 ± 0.1 [3] were obtained at zero external field in Ni 52 Mn 23 Ga 25 . It can be concluded that the agreement is quite good.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Our results can also be compared with acoustic emission measurements of Ludwig et al [2], as well as Niemann et al [3] where α = 2.6 and ε = 1.75 [2] as well as ε = 1.9 ± 0.1 [3] were obtained at zero external field in Ni 52 Mn 23 Ga 25 . It can be concluded that the agreement is quite good.…”
Section: Discussionsupporting
confidence: 50%
“…The evaluation method was similar to the one used in Ref. [2]. Since the heating and cooling were done in the DSC, it was possible to measure thermal signals simultaneously with acoustic emission.…”
Section: B Acoustic Emission Measurementsmentioning
confidence: 99%
See 3 more Smart Citations